Identification of two new core chromosome-encoded superantigens in Streptococcus pyogenes; speQ and speR - Reglinski,M; Sriskandan,S; Turner,CE (Journal of Infection, 2019)
Superantigens are ubiquitous within the Streptococcus pyogenes genome, which suggests that superantigen-mediated T-cell activation provides a significant selective advantage. S. pyogenes can carry a variable complement of the 11 known superantigens. We have identified two novel S. pyogenes superantigens, denoted speQ and speR, adjacent to each other in the core-chromosome of isolates belonging to eleven different emm-types. Although distinct from other superantigens, speQ and speR were most closely related to speK and speJ, respectively. Recombinant SPEQ and SPER were mitogenic towards human peripheral blood mononuclear cells at ng/ml concentrations, and SPER was found to be more mitogenic than SPEQ.